PRINSIP POLITIK YESUS DALAM RANGKA MEWUJUDKAN PERADABAN INJIL KERAJAAN ALLAH - Sostenis Nggebu; Edward Sitepu; Dominggus Pote; Okki Natanael; Edwin Gandaputra; Imanuel Kurnia (Phronesis: Jurnal Teologi dan Misi, 2023)
The problem of this article is that it examines the importance of understanding the political context at the time of Jesus's life, which became a challenge in His ministry. The Son of God offers true political principles compared to the motives of the socio-political movements of that time. The purpose of this article is to explain the political principles of Jesus to promote the values of the Kingdom of God. As a result, the political principle of Jesus offers human redemption to become citizens of God's Kingdom. Jesus' teachings became the standard that inspired the world order regarding love and truth as the main points of His message (Mk 1:15). In carrying out His redemptive mission, Jesus did not carry guns and swords. However, Jesus' political principles were based on love and truth. In conclusion, the essence of Jesus' politics emphasizes God's mercy for sinners.